KONTRIBUSI CULTURAL VALUES TERHADAP KECENDERUNGAN RESIDIVISME PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN KELAS IIA JEMBER - Handayani, Panca Kursistin; Ulva, Novita Sylvia; Maulida, Eva Fahmadia Jilan (Universitas Muhammadiyah Jember, 2019)
Research on recidivism tendencies which is influenced by internal factors that have been carried out is related to psychological problems (2014), self-regulation (2016) and self-control (2017). Based on this research it appears that there is a missing link related to the source of initial encouragement that comes from within the individual as a process of interaction and internalization of the initial experiences of individuals with parents, ancestors and other significant people. Related to this, this study aims to determine the effect of Cultural Value on the Trend of Recidivism in Jember Class IIA Prisoners.This type of research is associative quantitative that is to determine the relationship between one variable with another variable and the effect of a variable on other variables. There are two psychological scales used in this study, the Cultural Values scale adapted from The Potrait Value Questionnaire (PVQ-RR) compiled by Schwartz and the Residivism Tendency scale adapted from the Psychopathy Check List-Revised (PCL-R) compiled by Hare . The results of this study are expected to be input/reference in developing community values-based community intervention programs.The results showed a calculated F value of 0.471 with a significance level of 0.493> 0.05, which means that there was no influence of Cultural Value on the Trend of Residivism. Descriptive test shows that as many as 107 prisoners (56%) have high cultural values and 84 inmates (44%) have low cultural values. This means that prisoners tend to use cultural values as a reference in behavior, but they do not necessarily have compliance with the values that exist in the community. The highest percentage is the value of Universalism, Achievement, and Security. While the lowest percentage is the value of Stimulation, Benevolence Care, and Self Direction.